2020
DOI: 10.34172/ijhpm.2020.154
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Pathways Linking Populism to Ethnic Minority Health Comment on "A Scoping Review of Populist Radical Right Parties’ Influence on Welfare Policy and its Implications for Population Health in Europe"

Abstract: Based on a scoping review of empirical studies accompanied by interviews with experts, Rinaldi and Bekker studied the impact of populist radical right (PRR) parties on access to welfare provisions – the latter standing proxy for population health and for health inequalities in particular. We argue that populism can impact on migrant and ethnic minority health in multiple ways, in addition to the welfare mechanism specified in that review. These include institutionalised discrimination affecting individuals’ po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
1
Order By: Relevance
“…This is not necessarily something to look forward to, as it could lead to all kinds of invisible and unpredictable exclusions, in different places and against different kinds of others. 5 In this light, studying the relationship between populism and healthcare is of major importance. On this we fully agree with Rinaldi and Bekker and all other the scholars that have taken the opportunity to comment on their work.…”
Section: Resultsmentioning
confidence: 99%
“…This is not necessarily something to look forward to, as it could lead to all kinds of invisible and unpredictable exclusions, in different places and against different kinds of others. 5 In this light, studying the relationship between populism and healthcare is of major importance. On this we fully agree with Rinaldi and Bekker and all other the scholars that have taken the opportunity to comment on their work.…”
Section: Resultsmentioning
confidence: 99%
“…In this light, PRR policy preferences in these areas could be particularly harmful for already disadvantaged population groups, such workers on flexible contracts, small business owners and temporary migrant workers. [7][8][9][10] The European Union (EU) represents contradictory incentives. On the one hand potential protective power from EU judicial institutions might prevent PRR policies from being implemented, while on the other hand the single market encourages labour migration under conditions of limited social rights for migrant workers in countries of destination, exposing them disproportionally to risks (eg, COVID-19) without proper care (eg, equal access to vaccines).…”
Section: Prr Influence On Population Health Through Economic and Financial Policiesmentioning
confidence: 99%
“…4,5,7 Thirdly, we discuss the relevance of the PRR in relation to other policy areas that affect population health and health equity. [8][9][10] Global Manifestations, Definitions and Scope of Populism and Welfare Chauvinism Our scoping review revealed strong indications of welfare chauvinism, emphasising the nativist elements of the PRR agenda. Perhaps the most prominent contribution of the commentaries was a focus on populism -the hypothetical division between the 'people' and a corrupt elite.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…O atual desenvolvimento do populismo pode infl uenciar o processo de tomada de decisões políticas em vários níveis de governo 9 . Como resultado, as políticas de saúde pública podem ser discriminatórias e pôr em perigo muitas vidas, especialmente para grupos minoritários que há muito têm dificuldade em aceder aos serviços de saúde e estão cada vez mais em risco de discriminação 10 .…”
Section: Introductionunclassified